Unidocentes teachers perceptions about Physical Education and Pedagogical Residence Program interventions (Research, Society and Development, 2020)
The present work aimed to verify the perception of unidocentes of a public school in Uruguaiana/RS on Physical Education in the early years and the activities of the Pedagogical Residency Program UNIPAMPA. The subjects of this study were thirteen teachers in the initial interview and eleven in the final interview. After permission from the school management, was delivered a free and informed consent form for all unidocentes who had a resident working in their classes. All teachers accepted to participate in the study and answered a semi-structured interview before and after Physical Education classes taught by residents. The perceptions of the teachers participating in this study regarding the concept of Physical Education, point movement and development of motor skills as major categories. About the role of Physical Education in the early years, the emerging categories of the unidocentes responses were the development of cognitive skills and the development of psicomotricity. After the classes taught by the residents, of the eleven teachers, ten reported having noticed positive changes in the students. As for the expectation about the classes, nine teachers stated that it was contemplated, pointing out as main points the dynamic way of working, student motivation for classes and coherent planning. It is concluded that, the main benefits perceived by the unidocentes teachers about Physical Education classes with the residents, area teachers in training, concern the major stimulus provided for the development of students in the early years, in particular, in motor, cognitive and affective aspects.